Cleaner and controllable mechano-fenton-piranha oxidation of carbon nanotubes for energy application - Wei, Chaohui (2019)
The major sources of current energy consumption are fossil fuels, including coal, oil and natural gas, which have brought about serious environmental pollution, although renewable energies have been thought to be the replacement for years. Air pollution is one of the environmental issues, which has raised worldwide vigilance and concerns. Nitrogen oxides (NOx), from power plants, vehicles and material processing, is one of the serious anthropogenic pollutants because of their detrimental impact on the environment and livings on the earth. Thus, there are strict regulations on NOx emission, which in turn has frustrated the development of many innovative technologies. For example, the so-called sulfonitric acid (the mixture of concentrated H2SO4 and HNO3) is one of the most widely used oxidants for processing carbon nanotubes (CNTs), producing a large amount of NOx. As a result, the large scale of application of CNTs for downstream purpose remains challenging. In this research, a NOx-free oxidation method for CNTs processing has been proposed and demonstrated. Such newly treated CNTs were characterised by various physicochemical and electrochemical techniques to obtain the information comprising morphology, structural integrity, surface groups, suspension stability, conductivity (electrical and ionic) and charge storage capacity. Particularly, the properties of pristine and processed CNTs by sulfonitric oxidation were characterised for comparison reason. In addition, piranha oxidation of CNTs in an open reactor was also studied to help identify the suitable experimental parameters for later processes. CNTs from MFP oxidation, are relatively shorter, possess balanced surface OCGs without compromising the original CNT integrity, and disperse readily in water. Although the oxygen content of the CNTs from MFP oxidation was found to be lower than CNTs from sulfonitric oxidation, the original CNT structures were better preserved, consequently, desirable for making various CNT-composites, including those with conducting polymers for supercapacitors. The higher conductivity and better structural integrity of the CNTs processed by the new method were successfully transmitted to their corresponding polypyrrole (PPy) composites, which achieved higher specific capacitance than the composite with CNTs from sulfonitric oxidation. Moreover, the reactors in the process should be industrially adoptable, promising a great technological and commercial future.